2001
DOI: 10.1007/s002210100815
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between muscle output and functional MRI-measured brain activation

Abstract: The relationship between functional MRI (fMRI)-measured brain signal and muscle force and or electromyogram (EMG) is critical in interpreting fMRI data and understanding the control mechanisms of voluntary motor actions. We designed a system that could record joint force and surface EMG online with fMRI data. High-quality force and EMG data were obtained while maintaining the quality of the fMRI brain images. Using this system, we determined the relationship between fMRI-measured brain activation and handgrip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
216
3
4

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(253 citation statements)
references
References 53 publications
27
216
3
4
Order By: Relevance
“…In order to control for motor timing effects, we used a rhythm production task with alternating or equal force targets combined with alternating or equal interval targets. Previous functional imaging studies have shown a positive linear relationship between tapping rate and the spread of cortical activity for movement rates between 1 Hz and 5 Hz (Rao et al, 1996), and between force level and the amplitude of the measured fMRI signal, for forces between 20% and 65% of maximum (Dai et al, 2001). We controlled for these effects of rate and force level by setting the target time interval and force for the equal conditions to be the average of the values used in the alternating conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to control for motor timing effects, we used a rhythm production task with alternating or equal force targets combined with alternating or equal interval targets. Previous functional imaging studies have shown a positive linear relationship between tapping rate and the spread of cortical activity for movement rates between 1 Hz and 5 Hz (Rao et al, 1996), and between force level and the amplitude of the measured fMRI signal, for forces between 20% and 65% of maximum (Dai et al, 2001). We controlled for these effects of rate and force level by setting the target time interval and force for the equal conditions to be the average of the values used in the alternating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of sensory motor cortex (SMC) in a finger flexion force production task was observed to be greater in repetitive squeezing than in steady contraction (Thickbroom et al, 1999). In thumb-finger squeezing movements, increases in activation with force have been noted in MI (Cramer et al, 2002), SMA, PMC and cerebellum (Dai et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…A hypothetic answer is that the brain is a redundant organ that has multiple motor control centers with parallel projections to motoneuron pools in the spinal cord; the availability of multiple cortical centers controlling one motor task or muscle group makes "shifting of activation center" possible among these centers to compensate for fatigue. Numerous studies have shown multiple brain region activation even in controlling non-fatigue, simple motor tasks (e.g., Dai et al, 2001;Liu et al, 2003). The concept of activation shifting as a strategy to prolong a motor task under the condition of muscle fatigue has been presented for a long time with limited evidence showing rotation of motor units (Sogaard, 1995), muscles (Côté et al, 2002) and cortical neurons (Belhaj-Saïf et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Conductive strain gauges do not provide the ideal interface for monitoring torques and forces. Hydraulic solutions have been implemented (Dai et al, 2001;Liu et al, 2000;Vaillancourt et al, 2003), but there is no compact hydraulic solution for monitoring multiple DOF simultaneously. A similar method to the method described above has been implemented at the wrist, but did not suffer greatly from noise on the load cell recordings because the load cell was located further from the MR imaging region (Hidler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have used one-DOF devices in order to achieve this goal (Culham et al, 2003;Dai et al, 2001;Ehrsson et al, 2003;Floyer-Lea and Matthews, 2005;Liu et al, 2002;Vaillancourt et al, 2003). We implemented a method that permits researchers to quantitatively control experiments across joints and subjects.…”
Section: Future Directionsmentioning
confidence: 99%